Körperphantasien Technisierung - Optimierung - Transhumanismus - Beinsteiner, Andreas; Kohn, Tanja (innsbruck university press, 2016)
This anthology deals with current discussions around the mechanization and the optimization of the body up to the transhumanism. In the age of smartphones and social web, everyone can stage their lives and their bodies medially. With the possibilities of staging also increases the need for optimization. Cosmetic interventions are becoming more common, as well as the use of performance-enhancing and mood-lifting psychotropic drugs. The body becomes a product whose value is to increase in the labor market and in the sphere of the interpersonal. Never before has the wish seemed so great and so widespread to extend physical limits and stay young forever. The convergence of man and machine gives unprecedented power to those who provide the technologies and infrastructures: the potential to monitor and control human bodies is increasing. On this side of euphoria and paranoia, the question arises as to what drives the performance and optimization fantasies of our age. How can the interplay of bodies and technologies be adequately described in the 21st century?